2021
DOI: 10.1111/age.13064
|View full text |Cite
|
Sign up to set email alerts
|

Parsing the microRNA genetics basis regulating skeletal muscle fiber types and meat quality traits in pigs

Abstract: Muscle fibers are closely related to human diseases and livestock meat quality. However, the genetics basis of microRNAs (miRNAs) in regulating muscle fibers is not completely understood. In this study, we constructed the whole genome-wide miRNA expression profiles of porcine fast-twitch muscle [biceps femoris (Bf)] and slow-twitch muscle [soleus (Sol)], and identified hundreds of miRNAs, including four skeletal muscle-highly expressed miRNAs, ssc-miR-378, ssc-let-7f, ssc-miR-26a, and ssc-miR-27b-3p. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
3
8
0
Order By: Relevance
“…First, according to the observed muscle fiber characteristics, we selected PM and BF as representatives of type I muscle fibers (oxidative type) and type II muscle fibers (glycolytic type), respectively. Similar to previous reports, PM was characterized as the slow oxidative fiber type (type I), as found in pork [ 27 , 28 ], beef [ 29 ] and goat muscles [ 30 ], whereas BF showed higher respective percentages of type II fibers (fast-twitch fibers) [ 4 , 13 , 31 ]. Generally, the diameter of type I muscle fibers is thinner than that of type II muscle fibers [ 32 ], and our data were consistent with this pattern.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…First, according to the observed muscle fiber characteristics, we selected PM and BF as representatives of type I muscle fibers (oxidative type) and type II muscle fibers (glycolytic type), respectively. Similar to previous reports, PM was characterized as the slow oxidative fiber type (type I), as found in pork [ 27 , 28 ], beef [ 29 ] and goat muscles [ 30 ], whereas BF showed higher respective percentages of type II fibers (fast-twitch fibers) [ 4 , 13 , 31 ]. Generally, the diameter of type I muscle fibers is thinner than that of type II muscle fibers [ 32 ], and our data were consistent with this pattern.…”
Section: Discussionsupporting
confidence: 86%
“…MicroRNAs can regulate target gene expression by promoting mRNA degradation or repressing translation. Several studies have also identified some differentially expressed miRNAs between glycolytic and oxidative muscles [ 13 , 15 , 16 , 17 ]. At the miRNA level, the present study is the first to identify a total of 21 known DEmiRs in comparisons of PM (mainly composed of slow-twitch muscle fibers) and BF (mainly composed of fast-twitch muscle fibers).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study has found that miR-499-3p could suppress retinal cell proliferation while promote apoptosis to induce diabetic retinopathy by enhancing activation of the TLR4 signaling pathway [ 15 ]. In pigs, the expression of ssc-miR-499-3p was significantly correlated to the expression of myoglobin and pH, prompting its potential regulatory role in skeletal muscle fiber transformation and meat quality traits [ 16 ]. However, the exact biological function of miR-499-3p in skeletal muscle development has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic mutations in miR-208b and miR-1 precursor genes are significantly associated with pig muscle fiber characteristics and meat color traits ( 8 , 9 ). The expression of miR-499 is significantly correlated with the expression of myoglobin , which typically reflects meat color ( 10 ). However, few studies have explored the mechanism of miRNA involvement in the regulation of pig meat color traits.…”
Section: Introductionmentioning
confidence: 99%